Root-Associated Microbiota Response to Ecological Factors: Role of Soil Acidity in Enhancing Citrus Tolerance to Huanglongbing - Li, Bo; Wang, Yanan; Hu, Tongle; Qiu, Dewen; Francis, Frédéric; Wang, Shuangchao; Wang, Shutong (Frontiers in Plant Science, 2022)
The citrus orchards in southern China are widely threatened by low soil pH and Huanglongbing (HLB) prevalence. Notably, the lime application has been used to optimize soil pH, which is propitious to maintain root health and enhance HLB tolerance of citrus; however, little is known about the interactive effects of soil acidity on the soil properties and root-associated (rhizoplane and endosphere) microbial community of HLB-infected citrus orchard. In this study, the differences in microbial community structures and functions between the acidified and amended soils in the Gannan citrus orchard were investigated, which may represent the response of the host-associated microbiome in diseased roots and rhizoplane to dynamic soil acidity. Our findings demonstrated that the severity of soil acidification and aluminum toxicity was mitigated after soil improvement, accompanied by the increase in root activity and the decrease of HLB pathogen concentration in citrus roots. Additionally, the Illumina sequencing-based community analysis showed that the application of soil amendment enriched functional categories involved in host-microbe interactions and nitrogen and sulfur metabolisms in the HLB-infected citrus rhizoplane; and it also strongly altered root endophytic microbial community diversity and structure, which represented by the enrichment of beneficial microorganisms in diseased roots. These changes in rhizoplane-enriched functional properties and microbial composition may subsequently benefit the plant's health and tolerance to HLB disease. Overall, this study advances our understanding of the important role of root-associated microbiota changes and ecological factors, such as soil acidity, in delaying and alleviating HLB disease.